Dental health state in the 20 year-old population and more in Cienfuegos province. - Emma Gil Ojeda; Beatriz García Alpízar; Eduardo M. Curbeira Hernández; María de Los Angeles Sexto (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: The absence of consice data of some indicators in the stomatological subsystem of our province difficults the knowledge of the real situation of the dental health in our province population. Objetive: to determine some epidemiological indicators related to dental health in the 20 year-old population and more in Cienfuegos province. Method: a descriptive epidemiologcal study. Methods: 253 621 patients in a range of 20 years old and more. All health areas including municipalities were taken into consideration from May to June 2004. Results: The kind of denture more demanded for its rehabilitation by the population was the upper and the lower one. The highest indicators of cavities and exodonties were found in the 35 to 59 year-old group of patient as well as in the rural areas. The anatomic localization of cavity lesions were predominant in the posterior dental sector with a relation between sectors of 1:1,7. The lowest percetange in the covering range of stomatological attention was found in the 35 to 59 year-old group with 5 and 18 % in the majority of the municipalities. Conclusions: Through this investigation the behaviour of proposed indicators were evaluated as well as the necesities of treatment to establish future strategies of work in order to improve the dental health in the population.